-3(4p+4)-2(3-14p)=3(3+5p)

Simple and best practice solution for -3(4p+4)-2(3-14p)=3(3+5p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4p+4)-2(3-14p)=3(3+5p) equation:



-3(4p+4)-2(3-14p)=3(3+5p)
We move all terms to the left:
-3(4p+4)-2(3-14p)-(3(3+5p))=0
We add all the numbers together, and all the variables
-3(4p+4)-2(-14p+3)-(3(5p+3))=0
We multiply parentheses
-12p+28p-(3(5p+3))-12-6=0
We calculate terms in parentheses: -(3(5p+3)), so:
3(5p+3)
We multiply parentheses
15p+9
Back to the equation:
-(15p+9)
We add all the numbers together, and all the variables
16p-(15p+9)-18=0
We get rid of parentheses
16p-15p-9-18=0
We add all the numbers together, and all the variables
p-27=0
We move all terms containing p to the left, all other terms to the right
p=27

See similar equations:

| -20z-0.3=30z+1.4 | | 2x+4(x+3)=60 | | 2/11x+1/3=2/5-9/11x+2/5 | | -2+3x=-6x+9x | | 18W^2+2w-3=0 | | 4x+9=-36-8x | | 9/12=21/x | | 28x+4=40+8 | | −4(w+1)=−24w=w= | | 36x+36=40x+8 | | -36=-72+n | | n(4n+n)=39 | | 10x-158=3x-18 | | 1/3(6t-5)=t+5/6 | | 6x+29=6(3)+29 | | 9x-1+4x=14x-20 | | 4(1/3)x=260 | | 10+16x=7x+19 | | -2(m-7)=-22 | | 8x+x+7=16 | | 8x+24-2x=54 | | 4*1/3x=260 | | 3n^2-25n+48=0 | | 9x+4=5x+6 | | 41/3x=260 | | 39=x/5+11 | | 1/2n+1/2n+90=180 | | 2u-15=17 | | 5x+3-7(x+1)=7x+3 | | 36=-3(22-y)+(y-4) | | Y+x-22=180 | | 3(2x+50=8x+29 |

Equations solver categories